The Muslim Millennial family typology: the role of Muslim family circumflex model to avoid parents’ violent behavior against children in Indonesia - Supaat Supaat; Salmah Fa'atin (Indonesian Journal of Islam and Muslim Societies, 2019)
The shifting phenomena of a Muslim family function in the millennial era, in sociological perspective, require an effort of adjustment in the patterns of family behavior interactions. The role of family leader as the main breadwinner is not the only principle because a stay at home dad is one of alternatives for Indonesian couples to foster their family. Circumflex model on marital and family pattern system, according to Olson, is specifically designed for planning treatment and effective results on marital and family therapy. A healthy Muslim family will function properly including diminishing parents’ violent behavior against their children. This study explores the Muslim family typology in the millennial era based on Circumflex model in the dimensions of cohesion,adaptability, and communication, and respectively it encloses the roles of each type in reducing parents’ violent behavior against their children. This article occupies qualitative method and education psychological approach. Based on the interview and observation as the primary tools for data collection, this research reveals two findings. Firstly, the common Muslim family typology in millennial era based on Circumflex model includes the types of extreme, midrange, and balanced. In fact, the balanced type of Muslim family promotes appropriate functions in the dimensions of cohesion and adaptability. Secondly,the balanced type of Muslim family is capable to bring harmony to the family,and assist the individual to override the difficult time during the family life. Thus, it will eliminate the parents’ violence behavior to their children. Fenomena pergeseran fungsi keluarga muslim di era millenial, dalam prespektif sosiologi, menuntut upaya penyesuaian dalam pola interaksi perilaku keluarga. Peran kepala keluarga sebagai pencari nafkah tunggal tidak menjadi satusatunya acuan, karena pria menjadi bapak rumah tangga (stay at home dad) merupakan salah satu alternatif bagi beberapa pasangan dalam membangun suatu keluarga di Indonesia. Model sirkumpleks dari sistem pola keluarga dan perkawinan, menurut Olson, secara khusus dirancang untuk perencanaan treatment dan hasil yang efektif pada marital dan familiy therapy. Keluarga muslim yang “sehat” akan dapat berfungsi secara memadai, termasuk dalam upaya meredam perlaku kekerasan orangtua pada anak. Penelitian ini menelusuri tipe pola keluarga muslim di era millenial berdasarkan model sirkumpleks,yakni dimensi kedekatan keluarga (cohesion),dimensi adaptabilitas keluarga(adabtability) dan dimensi komunikasi (communication), kemudian mengungkap peranan masing-masing tipe dalam upaya meredam perilaku kekerasan orangtua pada anak. Artikel ini menggunakan metode kualitatif dan pendekatan Psikologi Pendidikan. Berdasarkan interview dan observasi sebagai alat utama pengumpulan data, penelitian ini menghasilkan beberapa temuan. Pertama,tipe umum pola keluarga muslim di era millenial berdasar model sirkumpleks adalah tipe ekstrem (extreme), tipe rentang tengah (mid range) dan tipe seimbang (balanced). Keluarga yang berfungsi memadai adalah keluarga yang bertipe seimbang dimensi kedekatan dan adabtabilitasnya. Kedua tipe tersebut yang mampu mewujudkan keharmonisan keluarga, dan sangat membantu individu dalam melewati masa-masa sulit ketika menemui problem kehidupan, sehingga meniscayakan perilaku kekerasan orangtua pada anak akan tereleminir.